Contemporary methods and technological advancements for evaluating the swiftness and precision of thrusts in swordsmanship - Britskiy V. A.; Aikin V. A. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to create a technological tool for training and assessment, the «Electronic-mechanical fencing target», and to demonstrate its effectiveness in evaluating the swiftness and precision of sword-based thrusts.